2020
DOI: 10.1002/pon.5341
|View full text |Cite
|
Sign up to set email alerts
|

Development of a communication and health literacy curriculum: Optimizing the informal cancer caregiver role

Abstract: Objective: The aim of this study was to develop learning objectives and identify content for a core communication and health literacy curriculum designed to optimize the role of informal cancer caregivers (family or friends). Methods:A three-step process was conducted: (a) two-round online Delphi method process with experts (n = 9) in cancer caregiving to gain consensus on curriculum learning objectives; (b) online survey of oncology providers (n = 32) to generate potential content and rate importance of domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…Whilst not being clinically significant, the CASP pleasure domain demonstrated a decline reported by non-caregivers but maintained static for caregivers over time. This may seem surprising, where caregiving is often perceived as a stressful not pleasurable activity [7,8]. However previous qualitative research has reported the positive experiences that caregiving can offer in some instances [28][29][30].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Whilst not being clinically significant, the CASP pleasure domain demonstrated a decline reported by non-caregivers but maintained static for caregivers over time. This may seem surprising, where caregiving is often perceived as a stressful not pleasurable activity [7,8]. However previous qualitative research has reported the positive experiences that caregiving can offer in some instances [28][29][30].…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, caregivers were not selected based on a specific illness or medical condition of the care-recipients. Previous evidence has frequently focused on examining informal caregiver outcomes for caregivers with specific diseases [8,11,19]. Accordingly, this analysis provides new insights to the wider community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Caregiver self-efficacy has been identified as an important component of a caregiver's coping, with higher caregiver self-efficacy associated with lower caregiver burnout and psychosocial distress as well improved patient well-being. 31 32 Wittenberg and colleagues 33 recently published a Delphi consensus curriculum for cancer caregivers identifying seven key areas for future intervention development, one of which focuses on caregivers working with health professionals, including preparing for consultations, sharing information, asking and prioritising questions and communicating patient need. A paucity of targeted education for cancer Open access caregivers to more confidently and skilfully engage with oncology clinicians remains.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…For example, the low health literacy of caregivers can cause incorrect clinical decisions affecting the child's treatment course. Moreover, the rate of going to emergency and hospitalization increases among them, and in general, they spend more medical costs (12,18). Health literacy is especially important for patients with cancer because decisionmaking for prevention, screening, and treatment in the oncology environment is complex.…”
Section: Introductionmentioning
confidence: 99%